Soldiers and Civil Power Supporting or Substituting Civil Authorities in Modern Peace Operations - Brocades Zaalberg, Thijs (Amsterdam University Press, 2006)
Peace operations became the core focus of many Western armed forces after the Cold War. The wish amongst political and military leaders during the 1990s to hold on to the classical identity of the armed forces as an instrument of force made them pursue a strict separation between military operations and the civilian aspects of peacekeeping, such as policing, administrative functions, and political and societal reconstruction. In his book Soldiers and Civil Power, Thijs Brocades Zaalberg argues that this policy failed to match up to reality. Supporting civil authorities, and at times even substituting them (de facto military governance), became the key to reaching any level of success in Cambodia, Somalia, Bosnia and Kosovo. As a result of the false segregation between the civilian and the military domain, this was accomplished mostly by improvisation and creativity of commanders who probed for the limiting boundaries of their original mandate by reaching ever further into the civilian sphere. This title is available in the OAPEN Library - http://www.oapen.org.